2014
DOI: 10.3109/07434618.2014.970294
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver Perceptions of Children who have Complex Communication Needs Following a Home-based Intervention Using Augmentative and Alternative Communication in Rural Kenya: An Intervention Note

Abstract: A high level of unmet communication need exists amongst children with developmental disabilities in sub-Saharan Africa. This study investigated preliminary evidence of the impact associated with a home-based, caregiver-implemented intervention employing AAC methods, with nine children in rural Kenya who have complex communication needs. The intervention used mainly locally-sourced low-tech materials, and was designed to make use of the child's strengths and the caregiver's natural expertise. A pretest-posttest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 47 publications
1
30
0
1
Order By: Relevance
“…Closely connected to this was the caregiver's changing perception of their child's disability and their personal situation. The caregivers perceived their child's disability as less severe, which is consistent with Bunning et al [59], even though no direct intervention was applied to the children. Furthermore, this extended to the caregiver's revised view that there was sufficient time and support to carry out their domestic duties.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Closely connected to this was the caregiver's changing perception of their child's disability and their personal situation. The caregivers perceived their child's disability as less severe, which is consistent with Bunning et al [59], even though no direct intervention was applied to the children. Furthermore, this extended to the caregiver's revised view that there was sufficient time and support to carry out their domestic duties.…”
Section: Discussionsupporting
confidence: 83%
“…Communication Disability Profile (CDP) [52]: Caregiver perceptions of the severity of their child's disability and extrinsic factors affecting their own capacity for caregiving, were captured. Adapted and shortened for an earlier study (CDP-brief version: see Bunning et al, 2014), it had been translated into Swahili and Giriama (local language) previously. Selected sections focusing on general domains rather than communication-specific content, were used.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Aspects of these issues have been raised in the AAC fi eld in general (e.g., Bunning, Gona, Newton, & Hartley, 2014). Going forward, it will be important to address the roles of more than one language and diverse cultures on the use of AAC for infants and young children.…”
Section: The Quality Of Evidence and Future Research Prioritiesmentioning
confidence: 98%
“…Eleven intervention studies were identified from SSA, nine from South Africa, one from Kenya, and one from Nigeria. Studies included single subject experimental designs [Akande, ; Travis & Geiger, ], pre‐post quasi‐experimental designs [Akande, ; Bunning, Gona, Newton, & Hartley, ; Pansegrouw & Alant, ; Silver, ], within‐subjects design with repeated measures [Alant et al, ], non‐experimental descriptive group designs of medication use [Louw, Bentley, Sorsdahl, & Adnams, ; Wong et al, ], and one qualitative design [Geils & Knoetze, ]. The sample sizes for experimental studies were very small with eight of the nine non‐pharmacological intervention studies having fewer than 10 participants.…”
Section: Interventions For Asdmentioning
confidence: 99%